Global urban temporal trends in fine particulate matter (PM2·5) and attributable health burdens: estimates from global datasets. Issue 2 (February 2022) - Southerland, Veronica A; Brauer, Michael; Mohegh, Arash; Hammer, Melanie S; van Donkelaar, Aaron; Martin, Randall V; Apte, Joshua S; Anenberg, Susan C
Summary: Background: With much of the world's population residing in urban areas, an understanding of air pollution exposures at the city level can inform mitigation approaches. Previous studies of global urban air pollution have not considered trends in air pollutant concentrations nor corresponding attributable mortality burdens. We aimed to estimate trends in fine particulate matter (PM2·5 ) concentrations and associated mortality for cities globally. Methods: We use high-resolution annual average PM2·5 concentrations, epidemiologically derived concentration response functions, and country-level baseline disease rates to estimate population-weighted PM2·5 concentrations and attributable cause-specific mortality in 13 160 urban centres between the years 2000 and 2019. Findings: Although regional averages of urban PM2·5 concentrations decreased between the years 2000 and 2019, we found considerable heterogeneity in trends of PM2·5 concentrations between urban areas. Approximately 86% (2·5 billion inhabitants) of urban inhabitants lived in urban areas that exceeded WHO's 2005 guideline annual average PM2·5 (10 μg/m 3 ), resulting in an excess of 1·8 million (95% CI 1·34 million–2·3 million) deaths in 2019. Regional averages of PM2·5 -attributable deaths increased in all regions except for Europe and the Americas, driven by changes in population numbers, age structures, and disease rates. In some cities, PM2·5 -attributable mortality increased despite decreases in PM2·5 concentrations, resulting from shifting age distributions and rates of non-communicable disease. Interpretation: Our study showed that, between the years 2000 and 2019, most of the world's urban population lived in areas with unhealthy levels of PM2·5, leading to substantial contributions to non-communicable disease burdens. Our results highlight that avoiding the large public health burden from urban PM2·5 will require strategies that reduce exposure through emissions mitigation, as well as strategies that reduce vulnerability to PM2·5 by improving overall public health. Funding: NASA, Wellcome Trust.